The Question of the Compatibility of Phenomenology and Naturalism in Shaun Gallagher’s Philosophy - Rimkevičius, Paulius; Gutauskas, Mintautas (Problemos, 2014)
The paper analyses Shaun Gallagher’s way of addressing the question of the compatibility of phenomenology and naturalism. The first part discusses Gallagher’s point of departure: the application of phenomenological conception of the body schema in an analysis of data acquired using the third-person approach. The second part discusses Gallagher’s broader project of naturalizing phenomenology: arguments supporting the idea that the naturalist programme should include not separate phenomenological insights but systematic application of the first-person approach. The third part discusses counterarguments to the naturalization of phenomenology. The authors claim that the main problem facing the philosopher trying to naturalize phenomenology is the naturalization of the phenomenology of thought. Finally, an attempt is made to describe the prospects of the project of naturalizing phenomenology.